(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
The aim of this analysis was to determine the relationship between high-involvement management and employee performance at deposit money banks in Rivers State, Nigeria. A cross sectional survey was used, which is a kind of quasi-experimental nature. The sample population consisted of 321 workers from 15 chosen deposit money banks. The cluster sampling method was used to select sample cases in this analysis. The study’s main data collection instrument was a questionnaire. The instrument was administered privately to the respondent. To evaluate the hypothesis, the retrieved data were evaluated using the Pearson product moment correlation coefficient statistical method. The moderating effect of workplace satisfaction on the relationship between high involvement management and employee performance was examined using partial correlation. The study showed an important connection between the aspects of high involvement management (incentives, capacity building, and employee participation) and indicators of employee performance (service quality and employee adaptability). Additionally, job satisfaction was found to be a major moderator of the link between high involvement management and employee performance. Thus, the analysis concluded that an employee’s performance would be enhanced by a personal interest in the tradition of high involvement management. Thus, the study proposed that deposit money bank management prioritize employees’ capacity-building needs in terms of preparation, as this would improve their performance in the enterprise.